Pengabdian Kukerta Membangun Desa di Desa Senggoro Kecamatan Bengkalis Kabupaten Bengkalis - Taryono Taryono; Septiani Rahayu; Rendy Alfaid; M.Gunawan; Priska Dian Cristina; Adia Pratama Dewi; Nurul Irdina; Muhammad Arsyad Syahputra; Amelia Agustina Putri; Aguslan Aguslan (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
Kukerta Building the Riau University Village in Senggoro Village, Bengkalis District, Bengkalis Regency is a form of community service activity. This Kukerta will be held from 10 July 2023 to 19 August 2023. This kukerta has several themes that can be taken as themes for work programs that will be implemented during the kukerta. These themes are one superior theme and three selected themes. This article discusses work programs that have been successfully implemented during the Kukerta. The method for implementing kukerta that has been implemented consists of carrying out surveys and planning work program activities that are in line with the chosen theme and the conditions and problems that exist in the village. Kukerta student work program activities are in line with existing work programs in the village government and receive support from the village government and also the local community. This is shown by the large number of students who are involved in village and community activities, and vice versa by the large number of students who involve the community and village government in their work program activities. forms of activities involving the village government, namely collaboration activities with the Senggoro village children's forum with go green and leisurely walking activities, mobile legends e-sports tournaments and we also participate in several village activities such as the Clean and Healthy Living Behavior Assessment event which was held in Senggoro Village and the Bengkalis Regent's visit to the Dara Sembilan Tomb on the occasion of the 511th Bengkalis Regency Anniversary. Meanwhile, forms of activities that involve the community include the socialization of several Micro, Small and Medium Enterprises (MSMEs), pious children's festivals, posyandu and mobile legend e-sports tournaments involving many local youth. Riau University Kukerta is expected to provide benefits to village communities and the local village government, especially those aimed at creating significant changes to the village and giving a good impression to the village.